Genome-wide analysis of mutations induced by carbon ion beam irradiation in cotton - Liu, Jianguang; Zhao, Guiyuan; Geng, Jinpeng; Geng, Zhao; Dou, Haikuan; Liu, Xu; An, Zetong; Zhang, Hanshuang; Wang, Yongqiang (Frontiers in Plant Science, 2023)
Carbon ion beam (CIB) irradiation is a powerful way to create mutations in animals, plants, and microbes. Research on the mutagenic effects and molecular mechanisms of radiation is an important and multidisciplinary issue. However, the effect of carbon ion radiation on cotton is uncertain. In this study, five different upland cotton varieties and five CIB doses were used to identify the half-lethal dose and thus the suitable irradiation dose for cotton. Analysis of the effect of half-lethal dose on mutation induction indicated that 200 Gy with LETmax of 226.9 KeV/μm was the most effective heavy-ion dose for upland cotton. Subsequently, three mutagenized progeny cotton lines from the wild-type strain Ji172 were re-sequenced. A total of 2959–4049 single-base substitutions (SBSs) and 610–947 insertion–deletion polymorphisms (InDels) were identified among the three mutants. Additionally, the ratio of transition to transversion in the three mutants ranged from 2.16 to 2.24. Among transversion events, G:C>C:G was significantly less common than three other types of mutations (A:T>C:G, A:T>T:A, and G:C>T:A). However, the proportions of six types of mutations were very similar in each mutant. The distributions of identified SBSs and InDels were similar; they were unevenly distributed across the genome and chromosomes. Some chromosomes had significantly more SBSs than other chromosomes, and there were “hotspot” regions of mutation on one or both ends. Overall, our study revealed a profile of cotton mutations caused by CIB irradiation, and these data could provide valuable information for cotton mutation breeding.